Fundus-controlled perimetry (microperimetry): Application as outcome measure in clinical trials. (May 2021) - Pfau, Maximilian; Jolly, Jasleen Kaur; Wu, Zhichao; Denniss, Jonathan; Lad, Eleonora M.; Guymer, Robyn H.; Fleckenstein, Monika; Holz, Frank G.; Schmitz-Valckenberg, Steffen
Abstract: Fundus-controlled perimetry (FCP, also called 'microperimetry') allows for spatially-resolved mapping of visual sensitivity and measurement of fixation stability, both in clinical practice as well as research. The accurate spatial characterization of visual function enabled by FCP can provide insightful information about disease severity and progression not reflected by best-corrected visual acuity in a large range of disorders. This is especially important for monitoring of retinal diseases that initially spare the central retina in earlier disease stages. Improved intra- and inter-session retest-variability through fundus-tracking and precise point-wise follow-up examinations even in patients with unstable fixation represent key advantages of these technique. The design of disease-specific test patterns and protocols reduces the burden of extensive and time-consuming FCP testing, permitting a more meaningful and focused application. Recent developments also allow for photoreceptor-specific testing through implementation of dark-adapted chromatic and photopic testing. A detailed understanding of the variety of available devices and test settings is a key prerequisite for the design and optimization of FCP protocols in future natural history studies and clinical trials. Accordingly, this review describes the theoretical and technical background of FCP, its prior application in clinical and research settings, data that qualify the application of FCP as an outcome measure in clinical trials as well as ongoing and future developments. Highlights: Fundus-controlled perimetry enables spatially-resolved testing of visual sensitivity. Through fundus-tracking, even patients with unstable fixation may be examined. Recent developments allow for partially photoreceptor-specific testing of function. Reliability and ability to detect change is evident for multiple retinal diseases. Applications include macular and retinal degenerations, dystrophies, toxic retinopathies and inflammatory diseases.